PENINGKATAN KEMAMPUAN KERJA SAMA SISWA DENGAN MENERAPKAN MODEL KOOPERATIF TIPE JIGSAW PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI SEKOLAH DASAR - Tanjung, Atikah; Joni; Indriyanto; Fauziddin; Syahrul Rizal, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students' collaborative skills through the implementation of the jigsaw cooperative model in Pancasila education, particularly regarding Indonesian culture. This study was a classroom action research (CAR) conducted in fifth grade at SDIT Nurul Ilmi Kulau in the even semester of the 2024/2025 academic year. The subjects were 23 students, consisting of 11 female students and 12 male students. The research procedure was conducted in two cycles, each consisting of planning, action implementation, observation, and reflection. Data collection techniques used included observation of teacher activities, observation of student activities, observation of student collaborative skills, documentation, and data analysis using qualitative and quantitative descriptive techniques. Based on the results of the data analysis, there was an increase in student collaborative activities in Pancasila education. The percentage of student cooperation in the pre-action phase was 55.00%, in cycle I, meeting 1, the percentage of student cooperation was 63.04%, in cycle I, meeting 2, the percentage of student cooperation was 71.09%, in cycle II, meeting 1, the percentage of student cooperation was 78.26%, and in cycle II, meeting 2, the percentage of student cooperation was 84.13%. The increase in students' cooperation skills from pre-action to cycle I was 12.07%, while in cycle I to cycle II it was 14.13%. Thus, it can be concluded that students' cooperation skills have improved by implementing the jigsaw cooperative model in Pancasila education subjects in elementary schools.